Lis pendens and Related Claims in Bilateral Agreements for Mutual Assistance in Civil and Commercial Cases Concluded Between Lithuania and Third Countries and Application of Articles 33–34 of the Brussels I Recast Regulation to the Bilateral Agreements in - Šekštelo, Albertas (Teisė, 2025)
Lithuania has concluded numerous bilateral agreements for mutual assistance in civil and commercial matters. Part of these agreements were concluded with post-Soviet states and contain provisions on lis (alibi) pendens, which govern the rules for navigating parallel proceedings in the Member States party to such bilateral agreements. However, the bilateral agreements remain silent on how to address concurrent proceedings where the judgment in proceedings before one State’s court will affect the outcome of proceedings before a foreign State’s court. The Brussels I Recast Regulation, in turn, introduced new mechanisms to prevent conflicting or irreconcilable judgments where both proceedings are pending before a third country’s court and the national court of a Member State of the European Union, as embodied in Articles 33 and 34 of the Regulation, respectively. This article will examine the lis pendens regime in the relevant bilateral agreements with third countries and analyze the interaction between such bilateral agreements and Articles 33–34 of the Brussels I Recast Regulation and other special regulations.